Thermoluminescent and Dosimetric Properties of Zirconium Dioxide Ceramics Irradiated with High Doses of Pulsed Electron Beam - Nikiforov S. A. Sergey Anatoljevich; Dauletbekova A. K. Alma Kezhemkulovna; Gerasimov M. A. Maksim Aleksandrovich; Kasatkina Ya. P. Yana Pavlovna; Denisova O. A. Olga Aleksandrovna; Lisitsyn V. M. Viktor Mikhailovich; Golkovsky M. G. Mikhail Gedalievich; Akylbekova A. Ayman; Bazarbek A. B. Asyl-Dastan Bazarbekuly; Akylbekov A. T. Abdrash Tasanovich; Popov A. I. Anatoly Ivanovich (2023, 2023)
Title screen